Mapeamento de mata ciliar em área de preservação permanente da microbacia do Córrego da Caçada - Castellan, Bruna Teixeira (2022)
Riparian forests are considered Areas of Permanent Preservation (APP) and they have an important role in soil conservation, preservation and conservation of biodiversity, mainly in the protection of the watersheds. From the perspective of territory management, all space planning requires analysis of the different components present in the environment. For this, geoprocessing can be used to enable the reduction of deficiencies in terms of compliance with environmental laws. This research becomes essential for addressing a theme directly related to the environmental issue and the current situation of society, since it is estimated that a considerable portion of these areas have been deforested, a fact that is characterized as an environmental crime. Thus, this work, through qualitative and quantitative parameters and the use of geotechnologies, aims to elaborate thematic maps that use CBERS-4a satellite images and QGIS free software as a tool. Through such tools, the objective is to feature the permanent preservation area of Córrego da Caçada watershed located in the municipality of Ituiutaba - Minas Gerais, in order to analyze the conservation status of PPAs’ source and watercourse in accordance with the provisions of the New Brazilian Forest Code, to later assess the possible environmental impacts associated with the non-preservation of the PPAs. For this, the following methodological procedures were used: bibliographic survey on the themes addressed; elaboration of thematic maps such as location, hydrography, preservation area, and land use and occupation; field visits to verify the information previously viewed in the thematic mappings; processing and manipulation of data in the QGIS free software; and finally, the delimitation of an equidistant area (buffer). The results achieved, showed that most of the delimited area of the watershed is outside the parameters established by the law, since there is no compliance with the preservation of native forest in most of the areas of its extension and it also enabled the verification of effectiveness regarding free geotechnology tools for this type of study.